Sulfate transporters in the plant’s response to drought and salinity: regulation and possible functions - Gallardo, Karine; Courty, Pierre-Emmanuel; Le Signor, Christine; Wipf, Daniel; Vernoud, Vanessa (Frontiers in Plant Science, 2014)
Drought and salinity are two frequently combined abiotic stresses that affect plant growth, development, and crop productivity. Sulfate, and molecules derived from this anion such as glutathione, play important roles in the intrinsic responses of plants to such abiotic stresses. Therefore, understanding how plants facing environmental constraints re-equilibrate the flux of sulfate between and within different tissues might uncover perspectives for improving tolerance against abiotic stresses. In this review, we took advantage of genomics and post-genomics resources available in Arabidopsis thaliana and in the model legume species Medicago truncatula to highlight and compare the regulation of sulfate transporter genes under drought and salt stress. We also discuss their possible function in the plant’s response and adaptation to abiotic stresses and present prospects about the potential benefits of mycorrhizal associations, which by facilitating sulfate uptake may assist plants to cope with abiotic stresses. Several transporters are highlighted in this review that appear promising targets for improving sulfate transport capacities of crops under fluctuating environmental conditions.